Comparison of atmospheric CO, CO2 and CH4 measurements at the Schneefernerhaus and the mountain ridge at Zugspitze - Hoheisel, Antje; Couret, Cedric; Hellack, Bryan; Schmidt, Martina (Atmospheric measurement techniques, 2023)
The CO, CO2 and CH4 mole fractions have been measured since 2002 at the Environmental Research Station Schneefernerhaus, which is located approximately 300 m below the summit of Zugspitze in the German Alps. Although the station is located remotely at an altitude of 2650 m a.s.l., local pollution events by snow blowers and snow groomers can be detected in the high temporal-resolution time series of seconds or minutes. Therefore, a time-consuming flagging process, carried out manually by the station manager, is necessary. - - To examine local influences and the effectiveness of data flagging, a 290 m long intake line to the higher Zugspitze ridge was used to measure CO, CO2 and CH4 mole fractions at a potentially less polluted location between October 2018 and October 2020. The comparison of these two time series shows that the mountain ridge measurement is almost unaffected by local pollution. It also demonstrates that the influence of local pollution events on the Schneefernerhaus measurements is successfully removed by the station manager. Only a small deviation of up to 0.24 ppm can be observed during the day between the CO2 time series of the Schneefernerhaus and the mountain ridge in winter, probably due to anthropogenic sources.